An=-4+3(n-1)

Simple and best practice solution for An=-4+3(n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for An=-4+3(n-1) equation:



A=-4+3(A-1)
We move all terms to the left:
A-(-4+3(A-1))=0
We calculate terms in parentheses: -(-4+3(A-1)), so:
-4+3(A-1)
determiningTheFunctionDomain 3(A-1)-4
We multiply parentheses
3A-3-4
We add all the numbers together, and all the variables
3A-7
Back to the equation:
-(3A-7)
We get rid of parentheses
A-3A+7=0
We add all the numbers together, and all the variables
-2A+7=0
We move all terms containing A to the left, all other terms to the right
-2A=-7
A=-7/-2
A=3+1/2

See similar equations:

| r/18=-25 | | 48-(3c+4)=2(c+7)=c | | 8z–13=2z+5 | | 9k=135 | | Y-450=4(x-15) | | 4x-10=1/3x | | 10k^2+5k-30=0 | | 1+5r-1+r=-18 | | n+216=-502 | | 2(4x-29)=(x-17) | | w/8=432 | | 7m-6=5M+10 | | -5(x+9=105. | | -5-5(5x+1)=-4x-31 | | 7m–6=5m+10 | | 3(2x+5)=9x+6-3x+9 | | 3/8a=-12 | | 7m–6=5m+10 | | Y21=x7 | | 2/5h-7=12/5=2h+3 | | 12x+34x=5-2.5x | | 25/x=55/77 | | 60x-18=6(10x-3) | | 39-3xx=10 | | 3(4x-8)=15x(35x+30) | | 7y-(3y-8)=20 | | p/2+11=20 | | 5x+30x-8=7(5x+8) | | 12=2k—8 | | 5(g-85)=10 | | 5(4-x)=-3+- | | 14+0.98p=19+0.78p |

Equations solver categories